A study of career opportunity : advancement, awareness and knowledge in Takaful industry / Noraini Mohamad - Mohamad, Noraini (2014)
The demand of Takaful products is increase positively and showed how potential this industry is in future. Thus, this phenomenon leads toward greater job opportunities such as position as Takaful operator or broker. This study using a convenience sampling done on 288 respondents in two selected campuses of higher learning institution in Kota Bharu, Kelantan. Questionnaires were personally distributed to examine the relationship of motivation, profession image and religiosity towards advancement, awareness and knowledge of career opportunity n Takaful industry. The results reveal that there are positive relationships between those variables. Several test of analysis has been done such as T-Test, Mann-Whitney, Kruskal-Wallis, correlation of coefficient and multiple regressions.